Differential expression of IGF components and insulin receptor isoforms in human seminoma versus normal testicular tissue - Neuvians, Tanja Pascale; Gashaw, Isabella; Hasenfus, Andrea; Häcker, Axel; Winterhager, Elke; Grobholz, Rainer (Neoplasia, 2005)
Insulin-like growth factors (IGF) have mitogenic and antiapoptotic functions, and may be involved in tumor growth. The purpose of the study was to investigate the role of IGF components in seminoma compared to normal testis. Normal testicular tissues from autopsy cases and seminoma from surgery cases were obtained for microarray and real-time reverse transcription polymerase chain reaction (RT-PCR) analysis of IGF-1, IGF-2, IGF receptor type 1 (IGF-R1), IGF-R2, insulin receptor isoforms A (IR-A) and B (IR-B), and IGF-binding proteins (IGFBP) 1-6. IGF-2 was localized by immunohistochemistry. IGFBP-5 protein expression was evaluated by Western blot analysis. mRNA expression in microarray and real-time RT-PCR showed similar tendencies: IGF-1, IGF-R1, IGF-R2, IR-A, and IGFBP-2 were not different in both groups. IGF-2, IR-B, IGFBP-1, IGFBP-4, and IGFBP-6 mRNA were downregulated in seminoma. IGFBP-3 tended to be upregulated in pT1 seminoma, but downregulated in pT2 stages. IGFBP-5 and IGF-2 protein expression correlated with mRNA expression. In conclusion, downregulation of mainly inhibiting IGFBPs may allow a stimulated tumor growth. The downregulated IGF-2 does not seem to be involved in the growth regulation of seminoma. Constantly expressed genes (e.g., IGF-1, IGF-R1, IR-A, and IGFBP-2) may reflect an involvement in spermatogenesis, but may also play a major role in tumor growth as their expression is not downregulated despite the lack of spermatogenesis in tumor tissue.